Treatment of Gold Mining Wastewater: A Review of Current Technologies and Future Perspectives - Mohammed U. GARBA; Usman B. ABDULLAHI; Hayatudden S. BARAYAIS; Aisha B. FARUQ; Suleiman IDRIS; Abubakar M. MUHAMMAD; Abubakar S. MOHAMMED (FUDMA Journal of Engineering and Technology, 2025)
Gold mining wastewater poses significant environmental risks due to its complex composition, including high concentrations of heavy metals, cyanide, sulphates, and acidic discharges. Effective treatment before release into the environment is essential to prevent long-term ecological and public health damage. This manuscript reviews the environmental impacts of gold mining wastewater and highlights current industrial-scale treatment technologies such as SAVMIN (Sulphate Removal Process), Slurry Precipitation and Recycle Reverse Osmosis (SPARRO), Biogenic Sulphide, and DESALX, which have been successfully commercialised in gold mining operations. These technologies integrate multiple separation processes for the efficient recovery of salts and over 95% of water for reuse, supporting sustainable mining practices. In addition, the study presents modern pilot-stage systems and laboratory-scale methods, particularly adsorption-based technologies, developed for the removal and recovery of precious and toxic metals from gold mine effluents. While many adsorbents have shown high removal efficiency, challenges remain in terms of adsorbent reusability, toxic sludge management, and economic feasibility. The need for integrating treatment systems that enable the simultaneous reclamation of water and recovery of gold and other valuable metals at low concentrations is emphasised as a step toward circular mine water use. The study concludes that for long-term sustainability, future gold mining wastewater treatment must address not only contaminant removal but also resource recovery, waste minimisation, and cost-effectiveness.
Keywords: Gold mining, heavy metals, technologies, treatment, wastewater.